Gledališki eksperiment na Slovenskem (1966–1986) in njegovi odmevi v mladinski dramatiki – Andrej Rozman Roza - Blažič, Milena (Amfiteater (Ljubljana), 2023)
In Slovenian (youth) literature, three authors who have worked in the field of drama and/or theatre stand out – namely, Svetlana Makarovič, academically trained actress (Sapramiška), Milan Jesih (Four Plays for Children, adaptations of Andersen’s fairy tales The Emperor’s New Clothes and The Ugly Duckling) and Andrej Rozman Roza. The paper will focus on the latter, who was strongly influenced by the theatre experiment in Slovenia, especially during the formative period of his studies of the Slovenian language (1974–1978). Andrej Rozman Roza (1956) started performing and/or publishing plays in the period 1981– 1990 (Inspector Schwake, 1986; collection of texts Ana Monró Theatre, 1991, etc.). He is known in literary history as a youth poet and is included in Slovenian language curricula (1998, 2011, 2018). However, the definition of a systemic author is more appropriate for him (I. Even Zohar, M. Dović) since of the six functions in the literary system (author, institution, market, repertoire, book, reader) he holds at least three roles (author, “institution”, book living book, etc.). This paper focuses on adaptations of classics of Slovenian (Cankar, Levstik, Linhart, Prešeren, etc.) or world literature that – regardless of literary genre or type – have become crossover literature in the process of literary reception, especially in picture-book editions (e.g., A Midsummer Night’s Dream which has the international fairy tale type number ATU 899A Pyramus and Thisbe). According to B. Kümmerling-Meibauer’s definition of crossover classics or authorship, Rozman is a crossover author. In addition, according to L. Hutcheon’s theory, adaptations are an important part of Rozman’s work and contribute to the updating of classics and modern classics. The paper presents the collection Brvi čez morje (The Footbridge Across the Sea), which contains thirteen plays, three of which are folktale texts – Janko and Metka (Hansel and Gretel) ATU 327, Obuti maček (Puss in Boots) ATU 545B, Vžigalnik (The Tinderbox) ATU 562 – and one which is a fairy tale, Kekec ATU 1137). Intertextually, they refer to folktale types
Keywords: A midsummer night’s dream; ATU 899A; crossover; gledališki eksperiment; mladinska drama; Piram in Tizba; Pyramus and Thisbe; Rozman Roza, Andrej; Rozman, Andrej; Sen kresne noči; Shakespeare, William; theatre experiment; večnaslovniška književnost; youth drama